Pengaruh Penerapan Prinsip GCG pada Persepsi Kualitas Informasi Keuangan PERUMDA Air Minum Tirta Sewaka Darma - Pratama Giri, Gede Rudi Harta; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p02, 2020)
The purpose of this study is to empirically assess the principle of transparency, accountability, accountability, independence and fairness/equality. This research was conducted at PERUMDA Air Minum Tirta Sewaka Darma with a quantitative approach that is in the form of associative. This research uses primary data of secondary data. A population of  3 4 0  employees and samples were selected using the purposive sampling technique of 56 employees. Data analysis techniques are double linear regression. Based on the results shows that transparency, accountability, responsibility, independence and fairness/equality influence positive and significant to the quality of financial information. Keywords: Transparency; Accountability; Responsibility, Independency; Fairness.